2010
DOI: 10.1111/j.1540-6261.2010.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Lucky CEOs and Lucky Directors

Abstract: We study the relation between opportunistic timing of option grants and corporate governance failures, focusing on "lucky" grants awarded at the lowest price of the grant month. Option grant practices were designed to provide lucky grants not only to executives but also to independent directors. Lucky grants to both CEOs and directors were the product of deliberate choices, not of firms' routines, and were timed to make them more profitable. Lucky grants are associated with higher CEO compensation from other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
206
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(215 citation statements)
references
References 42 publications
9
206
0
Order By: Relevance
“…Directors may struggle to perform in this monitoring role when the form of their compensation compromises their independence. The literature provides evidence that an improperly aligned compensation scheme, such as stock and stock options, compromises a director's independence and impairs their ability to provide objective oversight (Hamdani & Kraakman, 2007;Archambeault et al, 2008;Cullinan et al, 2008;Boumosleh, 2009;Bebchuk, Grinstein, & Peyer, 2010;Persons, 2012;Bierstaker, Cohen, DeZoort, & Hermanson, 2012 ).…”
Section: Compensation Of the Boardmentioning
confidence: 99%
See 1 more Smart Citation
“…Directors may struggle to perform in this monitoring role when the form of their compensation compromises their independence. The literature provides evidence that an improperly aligned compensation scheme, such as stock and stock options, compromises a director's independence and impairs their ability to provide objective oversight (Hamdani & Kraakman, 2007;Archambeault et al, 2008;Cullinan et al, 2008;Boumosleh, 2009;Bebchuk, Grinstein, & Peyer, 2010;Persons, 2012;Bierstaker, Cohen, DeZoort, & Hermanson, 2012 ).…”
Section: Compensation Of the Boardmentioning
confidence: 99%
“…Boumosleh (2009) found director stock options positively associated with earnings management and concluded that option compensation provides financial incentives for a director to fail to diligently monitor the financial reporting process. Bebchuk et al (2010) studied a duplicitous corporate practice that grants options to directors and CEOs when the stock prices were at their lowest value. The study finds that such "lucky grants" were back-dated from their actual grant date to maximize option value.…”
Section: Stock Option Compensationmentioning
confidence: 99%
“…Bebchuk, Grinstein, and Peyer (2010) show that opportunistic option timing is associated with a minority of independent directors on the board, the absence of an outside blockholder on the compensation committee, longer CEO tenure (a proxy for entrenchment), and higher overall CEO pay. Grants to independent directors were also opportunistically timed, and opportunistic timing for independent directors is associated with opportunistic timing for CEOs and also higher CEO pay.…”
mentioning
confidence: 99%
“…Anyway, the literature about a special group of managers was and is much smaller and (even) less conclusive (see for example Gregg, Machin and Szymanski, 1993, Clarke, Conyon and Peck, 1998, Yermack, 2005, Bebchuk, Grinstein and Peyer, 2010, and especially for Germany Fallgatter, 2003, Raible andVaupel, 2007). This group is formed by the non-executive directors (for an overview see Adams, Hermalin and Weisbach, 2010) or in a two-tier system like the German one (see de Plessis, 2004) by the members of the supervisory board (on both and their convergence see Hopt and Leyens, 2005).…”
Section: Introductionmentioning
confidence: 99%